2005
DOI: 10.1016/j.febslet.2005.05.072
|View full text |Cite
|
Sign up to set email alerts
|

Negative regulation of hypoxia inducible factor‐1α by necdin

Abstract: Hypoxia-inducible factor 1 (HIF-1) is a master transcription factor that mediates cellular and systemic homeostatic responses to reduce O 2 availability, such as erythropoiesis, angiogenesis, and glycolysis. Using the yeast two-hybrid screening system, we found that the oxygen dependent degradation (ODD) domain of HIF-1a interacts with necdin, a growth suppressor. The interaction of necdin with HIF-1a was confirmed using coimmunoprecipitation with the overexpressed HIF-1a. Biological effect of necdin on HIF-1a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
33
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(37 citation statements)
references
References 29 publications
4
33
0
Order By: Relevance
“…These findings suggest that the augmented apoptosis in the EGL in vivo of necdin-deficient cerebellum is attributable, at least in part, to the deregulation of the E2F1-Cdc2 system at early stages of CGN differentiation. Necdin interacts with various proteins involved in neuronal apoptosis such as p53, hypoxia-inducible factor-1␣, and the neurotrophin receptor p75 Tcherpakov et al, 2002;Kuwako et al, 2004;Moon et al, 2005). Thus, we cannot rule out the possibility that these necdin-interacting molecules other than E2F1-related cell cycle proteins are responsible for the enhanced apoptosis in vivo in the EGL of necdin-deficient mice.…”
Section: Both Cdc2 Expression and Apoptosis Are Increased In Necdindementioning
confidence: 90%
See 1 more Smart Citation
“…These findings suggest that the augmented apoptosis in the EGL in vivo of necdin-deficient cerebellum is attributable, at least in part, to the deregulation of the E2F1-Cdc2 system at early stages of CGN differentiation. Necdin interacts with various proteins involved in neuronal apoptosis such as p53, hypoxia-inducible factor-1␣, and the neurotrophin receptor p75 Tcherpakov et al, 2002;Kuwako et al, 2004;Moon et al, 2005). Thus, we cannot rule out the possibility that these necdin-interacting molecules other than E2F1-related cell cycle proteins are responsible for the enhanced apoptosis in vivo in the EGL of necdin-deficient mice.…”
Section: Both Cdc2 Expression and Apoptosis Are Increased In Necdindementioning
confidence: 90%
“…Necdin targets many regulatory proteins that control neuronal life-and-death and differentiation Kobayashi et al, 2002;Tcherpakov et al, 2002;Kuwajima et al, 2004Kuwajima et al, , 2006Kuwako et al, 2004Kuwako et al, , 2005Moon et al, 2005). Thus, necdin might serve as a hub protein in the network of proteinprotein interactions to promote and stabilize neuronal terminal differentiation.…”
Section: Both Cdc2 Expression and Apoptosis Are Increased In Necdindementioning
confidence: 99%
“…Three of these genes are of particular interest based on published literatures. Necdin (Ndn) is an imprinted transcription factor on chromosome 7 that has previously been implicated in cellular proliferation, collagen gene expression [25], and regulation of the metastasis-associated gene Hif1a [26,27]. Brd4, on chromosome 17, is a bromodomain-containing protein that associates with chromatin [17].…”
Section: Identification Of Ecm Eqtl Candidate Genesmentioning
confidence: 99%
“…Adhesion of tumor cells to endothelial cells is proposed to figure heavily in cancer metastasis and is involved in the vasculogenesis associated with tumor progression (Hakomori, 2002;Tei et al, 2002). It has been reported that MAGE-D1 is structurally homologous to necdin, which served as a postmitotic neuron-specific growth suppressor, induced growth arrest (Taniura et al, 1998) and could negatively regulate hypoxia inducible factor 1 α (HIF-1α) stability and angiogenesis (Moon et al, 2005). However, the relationship between MAGE-D1 and tumor cell migration and adhesion to endothelium in response to hypoxic stress has not been previously explored.…”
Section: Introductionmentioning
confidence: 96%